Nutritional Potential and Bioactive Compounds in Cereus jamacaru DC: An Multifaceted Cactus From Brazilian Semiarid - Almeida, Michelle Maylla Viana de; Araújo, Fernando dos Santos; Andrade, Alberício Pereira; Aquino, Pedro Gregório Vieira; Valença, Roberta de Lima; Bruno, Riselane de Lucêna Alcantara (Journal of Agricultural Studies, 2022)
Cereus jamacaru DC. is an endemic cactus of the Brazilian semiarid region empirically used by humans for forage, food and medicinal purposes. In this paper, we characterize the physicochemical and phytochemical profile of the C. jamacaru cladode and fruits, outlining their nutritional implications. We evaluate the basic physicochemical characteristic of the fruits and the main classes of chemical compounds present in aqueous and ethanolic extracts from cladode, peel, and pulp of ripe and semi-ripe fruits through qualitatively and quantitatively methods. We analyze the data through descriptive statistics and variance analysis. The fruits have appropriate pH, acidity, and total soluble solid levels for the fruit processing industry and fresh consumption. We identified the presence of saponins, tannins, flavones, flavonols, and xanthones in all samples, but alkaloids and steroids were both detected in cladodes exclusively. The phenolic compound and flavonoid contents vary according to the extraction method and sample class. The cladodes and pulp of ripe fruits have the highest flavonoid levels, while the content of phenolic compounds had a high level in peels of ripe and semi-ripe fruits. The presence of these bioactive compounds implies that C. jamacaru products have relevant pharmacological interest and functionality for human (fruits) and domestic ruminant (cladodes) food. These applications can boost the agricultural-economic exploration of C. jamacaru and contribute to income generation, and improve human and animal nutrition.